2007
DOI: 10.1080/03004430500375927
|View full text |Cite
|
Sign up to set email alerts
|

Effects of professional development training on joint attention engagement in low‐quality childcare centers

Abstract: This study carries forward the exploration of joint attention engagement in children from 18 to 24 months of age enrolled in 'low-quality' childcare centers. Childcare providers and children were videotaped to capture social interactions in the classroom including duration and bids for joint attention. One-half of 48 childcare providers were randomly assigned to receive professional development training (PDT) (the Focus-Follow-Talk ® technique) designed to increase the frequency of joint attention. Three month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…The reasons for the attrition in both groups varied; however, neither group differed significantly from the beginning group except on the variable of number of teacher changes (children) and length of employment (providers). These two differences are on artefact of remaining in the study for the duration (see Cain et al, 2007, for a detailed description of the attrition).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for the attrition in both groups varied; however, neither group differed significantly from the beginning group except on the variable of number of teacher changes (children) and length of employment (providers). These two differences are on artefact of remaining in the study for the duration (see Cain et al, 2007, for a detailed description of the attrition).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a study by Cain, Rudd, and Saxon (2007) found that child-care providers who had received training in joint attention engaged in more frequent and longer bouts of joint attention than the control group.…”
Section: Mitigating Factors Influencing Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Various combinations of coursework, workshops, in-class coaching, and mentoring have been found to promote greater sensitivity to children's needs (Cain, Rudd, & Saxon, 2007;Fiene, 2002), more effective teaching interactions (Hamre et al, 2012), increased reflection and intentional practice (Kagle, 2014), improved literacy routines (Byington, 2014;Neuman & Cunningham, 2009;Onchwari & Keengwe, 2008), and overall classroom quality (Burchinal, Cryer, Clifford, & Howes, 2002;Campbell & Milbourne, 2005;Romeyn, 2010) for teachers and assistant teachers in both center-and home-based child care settings. Coursework followed by inclassroom coaching was found to increase classroom math conversations for teachers with 4-year degrees in a university lab school (Rudd, Lambert, Satterwhite, & Smith, 2009).…”
Section: Professional Development To Enhance Math Talkmentioning
confidence: 97%
“…Various measures of engagement have been designed and used in research but there seem to be few measures that can be used by practitioners for measuring individual child engagement (Kishida & Kemp, 2006b). Also, while there is some evidence that practitioners can learn new skills, including observation skills, within a relatively short period (Cain, Rudd, & Saxon, 2007;Hasbrouck, 1997;McBride & Schwartz, 2003;Schepis, Reid, Ownbey, & Parsons, 2001), there seems to be little research targeting practitioners as observers of child engagement.…”
Section: Introductionmentioning
confidence: 97%